Detection and mapping of a lethal locus in a eucalyptus hybrid population - Rosado, Tatiana Barbosa; Tomaz, Rafael Simões; Rocha, Rodrigo Barros; Rosado, Antônio Marcos; Alves, Alexandre Alonso; de Araújo, Elza Fernandes; Alfenas, Acelino Couto; Cruz, Cosme Damião (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to verify the existence of a lethal locus in a eucalyptus hybrid population, and to quantify the segregation distortion in the linkage group 3 of the Eucalyptus genome. A E. grandis x E. urophylla hybrid population, which segregates for rust resistance, was genotyped with 19 microsatellite markers belonging to linkage group 3 of the Eucalyptus genome. To quantify the segregation distortion, maximum likelihood (ML) models, specific to outbreeding populations, were used. These models consider the observed marker genotypes and the lethal locus viability as parameters. The ML solutions were obtained using the expectation‑maximization algorithm. A lethal locus in the linkage group 3 was verified and mapped, with high confidence, between the microssatellites EMBRA 189 e EMBRA 122. This lethal locus causes an intense gametic selection from the male side. Its map position is 25 cM from the locus which controls the rust resistance in this population.